Catalogue of the mite family Podocinidae Berlese (Acari: Mesostigmata) - Barros, Avyla R. A.; Castilho, Raphael C.; de Moraes, Gilberto J. (Zootaxa, 2020)
The mite family Podocinidae consists of 38 species in three genera, namely Africoseius Krantz (two species), Podocinella Evans & Hyatt (five species) and Podocinum Berlese (31 species). They are free living, but their biology is poorly known. The objective of this work was to summarise the history of the classification of the podocinids, to provide a brief diagnosis of the family, a key to the genera, and to assemble the scattered taxonomic information about the species and the genera in which they are placed.